Design and Experimental Testing of Holly Pruning Machine with Adaptive Adjustment Tool - Xiuhao Yu; Chengming Hou; Liqi Qiu; Xuesong Li; Penghui Yao; Ying Zhao (BioResources)
To improve the efficiency of holly pruning, effectively solve the labor intensity of manual handheld pruning machines, and the frequent replacement of tools when pruning different shapes of hollies, this study designed a pruning machine with adaptive tool adjustment. A combination of theoretical calculations, fluid dynamics simulation and analysis, and field testing was employed to design spray application mechanisms and verify their feasibility. Visual distance measurement and target recognition algorithms were used to design visual mechanisms, which were experimentally validated. Based on the principles of kinematics and dynamic simulation analysis, adaptive tool adjustment mechanisms were designed, and the key factors influencing the pruning smoothness rate and residual branch rate of the pruning equipment were identified. Based on the force analysis and parameters from the experimental results, the machine performed well, with a cutting mechanism motor speed of 20.9 kr/min, a tool tilt angle of 50°, and a walking speed of 0.91 m/s. The machine achieved a pruning smoothness rate of 79.3% and a residual branch rate of 8.1%, thereby meeting the requirements for holly pruning in horticultural operations.